Finishing properties of polyurethane and acid catalyst coating on bamboo strip board / Norashikin Kamarudin … [et al.] - Kamarudin, Norashikin; Rosman, Norhafizah; Mahmud, Siti Zalifah; Nik Hashim, Nik Hazlan; Mokhtar, Norain (2012)
Finishing process is the last of a sequence of manufacturing actions. The application of finishes is to protect the surface and also enhance the aesthetic value of bamboo strips board. Finishing also helps to enhance the attractiveness of the surface texture, dimensional stability and durability. In this study, bamboo strips board was used as a panel commercial. It used to substitute the shortage of the other plywood but I.D information about the finishing on bamboo strips board. This study carried out the suitability of three types of finishing material such as polyurethane and acid catalyst lacquer. From this study, polyurethane lacquer shows good a resistance against gloss and hardness but slightly poor for the impact, crosscut and household Acid catalyst lacquer shows a good performance on the impact, crosscut and household but slightly poor for hardness and gloss. It is very suitable to make kitchen cabinet and dining table.